Hong Kong activist Anna Kwok’s father is being prosecuted as a form of ‘collective punishment,’ according to rights groups - Oiwan Lam (Global Voices, 2025)
Kwok Yin-sang's prosecution has shocked overseas Hong Kong communities, as he was the first relative of a wanted activist charged under the security law, Hong Kong's latest strategy of collective punishment.
Asia